Qualitative Insights on Barriers to Receiving a Second Dose of Measles-Containing Vaccine (MCV2), Oromia Region of Ethiopia - Kalkidan Solomon; Brooke N. Aksnes; Abyot Bekele Woyessa; Chala Gari Sadi; Almea M. Matanock; Monica P. Shah; Paulos Samuel; Bekana Tolera; Birhanu Kenate; Abebe Bekele; Tesfaye Deti; Getachew Wako; et al. (Vaccines)
Introduction: Ethiopia introduced a second dose of measles-containing vaccine (MCV2) in 2019 to provide further protection against measles and further progress toward elimination. However, the sub-optimal coverage of both MCV1 and MCV2 suggest challenges with vaccine uptake. In this qualitative study, we explored barriers to the uptake of MCV2 among caregivers, community leaders, and healthcare workers (HCWs). Method: A qualitative study was conducted between mid-April and mid-May 2021. We selected ten woredas (districts) in the Oromia Region, Ethiopia, stratified by settlement type (urban/rural), MCV1 coverage (high ≥ 80%; low < 80%), and history of measles outbreaks between June 2019 and June 2020. Experiences surrounding barriers to MCV2 uptake were discussed via focus group discussions (FGDs) and in-depth interviews (IDIs) with caregivers of children 12–23 and 24–36 months and key informant interviews (KIIs) with HCWs who administer vaccines and with community leaders. Participants were recruited via snowball sampling. Recorded data were transcribed, translated to English, and analyzed using ATLAS.ti v.09. Results: Forty FGDs and 60 IDIs with caregivers, 60 IDIs with HCWs, and 30 KIIs with community leaders were conducted. Barriers among caregivers included lack of knowledge and awareness about MCV2 and the vaccination schedule, competing priorities, long wait times at health facilities, vaccine unavailability, negative interactions with HCWs, and transportation challenges. At the community level, trusted leaders felt they lacked adequate knowledge about MCV2 to address caretakers’ questions and community misconceptions. HCWs felt additional training on MCV2 would prepare them to better respond to caretakers’ concerns. Health system barriers identified included the lack of human, material, and financial resources to deliver vaccines and provide immunization outreach services, which caretakers reported as their preferred way of accessing immunization. Conclusions: Barriers to MCV2 uptake occur at multiple levels of immunization service delivery. Strategies to address these barriers include tools to help caretakers track appointments, enhanced community engagement, HCW training to improve provider–client interactions and MCV2 knowledge, and efforts to manage HCW workload.